Edmund Bergler papers - Bergler, Edmund, 1899-1962.
Correspondence consisting primarily of letters from Bergler to Mrs. Walter Charak in which he discussed his writings as well as hers. Includes reprints of articles on psychiatric and psychoanalytic subjects written by Bergler between 1943 and 1948.
Psychiatrist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Charak, Walter, -- Mrs. -- Correspondence; Psychiatry; Psychoanalysis; Psychiatrists